Hubungan antara persepsi kualitas hubungan romantis orang tua dan kualitas hubungan romantis mahasiswa di Malang - Trisna Aulia Nur Rakhmah; Farah Farida Tantiani (SOSIOHUMANIORA: Jurnal Ilmiah Ilmu Sosial dan Humaniora, 2024)
In a romantic relationship, the quality of a romantic relationship is one of the factors that can maintain a relationship, where individuals subjectively evaluate the relationship carried out with their partner. The quality of romantic relationships can also be influenced by the family especially in terms of relating to others because parents are considered important and are models for their children. This study aims to determine whether or not there is a relationship between the perception of the quality of romantic relationships of parents and the quality of romantic relationships among students in Malang. This research method uses a correlational quantitative method approach on 402 students in Malang aged 18-25 years. The data collection instrument used The Parental Relationship Evaluation Questionnaire (PRE) with 34 items (α = .986) and The Perceived Relationship Quality Component (PRQC) with 17 valid items (α = .944) which have been translated into Indonesian. The sampling technique uses convenience sampling with the Spearman Rank correlation test analysis technique. The results of this study showed that there was a significant relationship with a value of .160 between the Perception of the Quality of Romantic Relationships of Parents with the Quality of Romantic Relationships of Students in Malang with the direction of a positive relationship. This means that the lower the quality of romantic relationships of students, the lower the perception of the quality of romantic relationships of parents and vice versa.